Application of coke breeze for removal of colour from coke plant wastewater. (15th January 2022) - Ghosh, Tamal Kanti; Biswas, Pinakpani; Bhunia, Prasenjit; kadukar, Sameer; Banerjee, Saroj Kumar; Ghosh, Rita; Sarkar, Supriya
Abstract: Treatment of coking waste water has always been a challenge because of its complex and toxic nature. Numbers of technologies like biological treatment, advanced oxidation processes, activated carbon treatment etc. are available for removal of color and organic contaminants from wastewater. However, challenges and problems associated with application of biological, advanced oxidation methods for removal of color, chemical oxygen demand (COD), cyanides led to thrust for the development of new promising technologies. In this study, the application of coke breeze for the treatment of wastewater through adsorption has been demonstrated. A pseudo second order reaction kinetics has been observed through batch process adsorption study. Furthermore, adsorption data has found to be best fitted with the Freundlich adsorption isotherm model. Color removal efficiency of 80–90% along with COD removal efficiency of 40–50% was observed within 30 min by 120 g/L dosage of the adsorbent. The removal of phenolic and other organic compounds from coking wastewater has been measured through UV–Vis spectroscopy. The morphological changes of the adsorbent coke breeze have been captured through scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) analysis. However, because of the significant abundance in the steel plant, cost effectiveness and applicability of the post-treated coke breeze in sintered plant as fuel, turn it into a suitable adsorbent despite of having much lower specific surface area compared to commercial activated carbon (AC). Therefore, application of the coke breeze turns it into a very promising material and the technique is sustainable towards the coke quenching effluent treatment. Highlights: Coke breeze, a non-utilized part of steel making process is applied for removal of colour from coke plant wastewater. Coke breeze dosage rate of 120 gL − 1 could remove 80–90% of color and 40–50% of COD within 30 minutes. UV, SEM, EDX spectra indicated the removal of phenols and other organic compounds from coking waste water. Reaction kinetics measurement indicated a pseudo 2nd order adsorption reaction process. Coke breeze is found to be the cheapest adsorbent for coke plant waste water treatment due to its ready availability.